2020
DOI: 10.1177/0300060520936829
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of bacteremic brucellosis

Abstract: Objective To retrospectively investigate the epidemiological features, clinical manifestations and laboratory characteristics of bacteremic brucellosis. Methods Brucellosis patients admitted to our clinic from January 2015 to December 2017 were included in the study. Patient electronic medical records were reviewed for epidemiological features, clinical manifestations, and laboratory findings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Previous studies have reported increased liver enzymes and elevated CRP in patients with B. bacteremia . 6 19 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported increased liver enzymes and elevated CRP in patients with B. bacteremia . 6 19 21 22…”
Section: Discussionmentioning
confidence: 99%
“…Although brucella-associated bacteremia is not uncommon, few cases of brucellosis presenting with bacteremia and acute sepsis remains in the literature [12] . Brucellosis may frequently present with cytopenia, particularly during febrile bacteremia.However, pancytopenia is not a common presenting symptom [6] .…”
Section: Introductionmentioning
confidence: 99%
“…14 From previous studies, several clinical manifestations, and laboratory results were found to be associated with bacteremic brucellosis, including fever, chills, leukopenia, thrombocytopenia, increased liver enzymes, and elevated C-reactive protein levels. 15,16 Although Brucella bacteremia is not uncommon in patients with Brucellosis, the reports regarding brucella bacteremia are scarce in Anhui Province. Furthermore, results obtained from the epidemiology, laboratory tests, and the clinical presentation of brucellosis patients are not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 14 From previous studies, several clinical manifestations, and laboratory results were found to be associated with bacteremic brucellosis, including fever, chills, leukopenia, thrombocytopenia, increased liver enzymes, and elevated C-reactive protein levels. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%